2021
DOI: 10.3332/ecancer.2021.1238
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-oncology in the Philippines: a scoping review on the state of medical practice, deterrents to care and therapeutic gaps

Abstract: Background: Neoplasms of the brain and spine are relatively uncommon compared to breast, lung and gastrointestinal tumours, which occur at higher rates in the Asian population. Updated guidelines in diagnosis and treatment of neuro-oncologic diseases recommend advanced molecular-based precision-medicine; thus the need for increasingly individualised regimens. It is, therefore, necessary to determine whether there are areas of improvement in the provision of care to these patients, especially in low-to middlein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
(34 reference statements)
1
10
0
Order By: Relevance
“…This inadequate coverage of government-led health care financing led the majority of Filipinos to spend from their own pockets. These findings are in line with the recent studies addressing the gaps in the management of different neurologic diseases (Parkinson's disease, primary brain tumor, multiple sclerosis, epilepsy, stroke) in the Philippines (23,33,(42)(43)(44).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This inadequate coverage of government-led health care financing led the majority of Filipinos to spend from their own pockets. These findings are in line with the recent studies addressing the gaps in the management of different neurologic diseases (Parkinson's disease, primary brain tumor, multiple sclerosis, epilepsy, stroke) in the Philippines (23,33,(42)(43)(44).…”
Section: Discussionsupporting
confidence: 88%
“…As of 2016, there are only around 78 MRI units (0.8 MRI units per online million population) in the country operated by public and private sectors, and the majority are located in Manila (22). Cranial MRI with contrast usually costs around USD 103-618 (33). There are only seven institutions that offer FDG-PET scans in the country and the price ranges from USD 604-1000.…”
Section: Challenges In Diagnosismentioning
confidence: 99%
“…The investigators attribute this high mortality in our study to a difference in healthcare systems. In the Philippines the universal health care law is partially and poorly implemented ( 14 ) and majority of the Filipinos belong to the lower socioeconomic status ( 15 ). Since 1992, the Philippine Government has devolved the management and delivery of health services from the national Department of Health to locally elected provincial, city, and municipal governments.…”
Section: Discussionmentioning
confidence: 99%
“…This was highlighted in a review of studies on the health care cost and financing of patients with malignancies (especially for those with central nervous system malignancies). The cost of care (especially in cancer care) in the country is not covered by most insurance companies and is scarcely subsidized by the state, which means that cancer care is an out-of-pocket cost for most if not all Filipinos ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies exploring treatment gaps for various neurological diseases in the country have shown a want of health information in the form of research. These studies cite a lack of local epidemiologic data and local experience with diagnosis or treatment for autoimmune encephalitis, bacterial meningitis, brain tumors, epilepsy, multiple sclerosis, Parkinson’s disease, and even stroke [ 14 , 15 , 16 , 17 , 18 , 19 ]. By further evaluating research performance, we can identify systemic disparities and guide appropriate solutions and direction for further study.…”
Section: Introductionmentioning
confidence: 99%